EXPLORING THE HIDDEN DEPTHS: IDENTIFYING AND MAPPING CAVES IN SOUTH MALANG'S KARST AREA FOR SPECIAL INTEREST TOURIST ATTRACTIONS - Mohammad Ainul LABIB; Alfi SAHRINA; Fatiya ROSYIDA; Adip WAHYUDI; Ho Nhu NGOC; Galih Fajar SUKOCO; Mohamad Fuad CHABIB (Geo Journal of Tourism and Geosites)
The aim of this research is exploring through identifying the cave landscape and mapping around the Coban Perawan Cave for special interest tourism object. The method used in this research was field survey by plotting the entrance area which was used to determine the location and coordinate control during cave mapping. The results of the cave mapping were then processed using survex software and geographic information systems. The cave passage landscape was portrayed in the form of a cave map and presented with a geographic information system to show the connection between the cave passages. Mathematical calculations of the cave passage were also used to determine the size of the cave passage, these include cave passage's lenght, depth, width and volume. Cave dimensions were used as a comparison of the width and height of the cave passage to see the spatial conditions and shape of the cave passage. Furthermore, the results of the analysis on special interest tourism objects by looking at the condition of the cave surface, cave passages, the accessibility, the level of difficulty of the cave and the facilities are presented in a descriptive table. The results of the research show that there is a single passage that is not connected to other caves, except the Pramuka Cave which is possible to connect with other caves. The mapping results showed that there are vertical passages in the study area and also single horizontal passages. Besides, there is also a combination of vertical and horizontal passages. The dimensions of the caves in the cave passage segment show that the cave passage has a tendency to having circular dimensions or forming a chamber, but there are also narrow passages. In Pramuka Cave Block, there is tendency of having a connection between the cave passages and the Coban Perawan Cave Block due to the existence of the connection of its hydrological system to other caves.The existence of these caves in the study area certainly has educational value and its uniqueness that can be utilized in special interest tourism attraction.